Integument Mycobiota of Wild European Hedgehogs (Erinaceus europaeus) from Catalonia, Spain. (25th September 2012) - Molina-López, R. A.; Adelantado, C.; Arosemena, E. L.; Obón, E.; Darwich, L.; Calvo, M. A.
Abstract : There are some reports about the risk of manipulating wild hedgehogs since they can be reservoirs of potential zoonotic agents like dermatophytes. The aim of this study was to describe the integument mycobiota, with special attention to dermatophytes of wild European hedgehogs. Samples from spines and fur were cultured separately in Sabouraud dextrose agar (SDA) with antibiotic and dermatophyte test medium (DTM) plates. Nineteen different fungal genera were isolated from 91 cultures of 102 hedgehogs. The most prevalent genera were Cladosporium (79.1%), Penicillium (74.7%), Alternaria (64.8%), and Rhizopus (63.7%). A lower prevalence of Aspergillus (P = 0, 035 ; χ 2 = 8, 633 ) and Arthrinium (P = 0, 043 ; χ 2 = 8, 173 ) was isolated during the spring time and higher frequencies of Fusarium (P = 0, 015 ; χ 2 = 10, 533 ) during the autumn. The prevalence of Acremonium was significantly higher in young animals (70%, 26/37) than in adults (30%, 11/37) (P = 0, 019 ; χ 2 = 5, 915 ). Moreover, the majority of the saprophytic species that grew at the SDA culture were also detected at the DTM. Finally, no cases of ringworm were diagnosed and no dermatophytes spp. were isolated. Concluding, this study provides the first description of fungal mycobiota of the integument of wild European hedgehogs in Spain, showing a large number of saprophytic species and the absence of dermatophytes.